Development of a logistics strategy for the enterprise - Chuanbing, Li (Харківський національний автомобільно-дорожній університет, 2024)
In the qualification work, the economic activities of JSC «Vostok» were analyzed, including an organizational characterization of the company, the evaluation of its diversification efforts, and an assessment of the quality of its insurance services. For the first time, theoretical and methodological foundations of strategic management through diversification were substantiated, taking into account the specific conditions of the insurance services market in Ukraine. A comprehensive approach to improving insurance services was proposed, emphasizing the application of innovative tools, including blockchain technology, to enhance efficiency and digitalization processes in the field of auto insurance. Practical recommendations were developed for expanding the diversification of services, and an evaluation of their economic effectiveness was conducted, which confirmed the feasibility of implementing the proposed measures. Predictive assumptions – the results of this study can be applied to improve the strategic management processes of insurance companies and other enterprises operating in unstable market conditions, ensuring their adaptability, competitiveness, and sustainable development.
Keywords: diversification; strategic management; insurance company; insurance services; blockchain; innovation